Pandemic detention: life with COVID-19 behind bars in Maryland - Arscott, Joyell; Doan, Brandon; Dayton, Lauren; Eber, Gabriel B.; Sufrin, Carolyn B.; Beyrer, Chris; Rubenstein, Leonard (Frontiers in Public Health, 2023)
Background People incarcerated during the COVID-19 pandemic face higher vulnerability to infection due to structural and social factors in carceral settings. Additionally, due to the higher prevalence of chronic health conditions among carceral populations, they are also at risk for more severe COVID-19 disease. This study was designed to explore the experiences of people incarcerated in prisons and jails in Maryland during the height of the pandemic. Methods We conducted semi-structured phone interviews between January 2021 and April 2022 with ten individuals incarcerated in Maryland carceral facilities during the height of the U.S. COVID-19 pandemic and were subsequently released from prison or jail. We transcribed the interviews, coded them, and engaged in content analysis, an inductive analytical approach to developing themes and meaning from qualitative data. Results Four themes emerged from participants’ descriptions of their experiences: (1) distress from fear, vulnerability, and lack of knowledge about COVID-19 and how to protect themselves, (2) shortcomings of prison and jail administrators and other personnel through lack of transparency and arbitrary and punitive enforcement of COVID-19 protocols, (3) lack of access to programming and communication with others, and (4) absence of preparation for release and access to usual re-entry services. Conclusion Participants responded that the prison and jails’ response during the COVID-19 pandemic was ill-prepared, inconsistent, and without appropriate measures to mitigate restrictions on liberty and prepare them for release. The lack of information sharing amplified their sense of fear and vulnerability unique to their incarceration status. Study findings have several institutional implications, such as requiring carceral facilities to establish public health preparedness procedures and making plans publicly available.